A modern mine? Greenlandic media coverage on the mining community of Qullissat, western Greenland, 1942–1968. Issue 1 (2nd January 2018) - Priebe, Janina
Abstract: During the first half of the twentieth century, the coalmine of Qullissat on Disko Island in western Greenland was at the centre of visions of an industrial future for the then Danish dependency. The closure of the mine and resettlement of the community in 1972 was thus marked by confusion, and became a key event in the political development of modern Greenland. This qualitative study analyses the representation of Qullissat in two Greenlandic newspapers, Grønlandsposten and Atuagagdliutit/Grønlandsposten, between 1942 and 1968. It seeks to add a layer of understanding to the history of the mining community by drawing attention to the framing of Qullissat's future in public discourse, using newspapers as a historical source. During the Second World War and well into the 1950s, media coverage of Qullissat focused on the modernisation measures initiated by the Danish mine management based on expert assessments. From the mid-1960s, however, the representations of Greenlandic workers as not matching modern industrial ideas created the impression of a community that was no longer viable in the postcolonial setting. In many respects, this media discourse reflects a perceived dichotomy between Denmark as a modern society, and Greenland as non-modern and dependent.